Association of E484K Spike Protein Mutation With Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection in Vaccinated Persons: Maryland, January–May 2021. (2nd September 2021) - Feder, Kenneth A; Patel, Ami; Vepachedu, Venkata R; Dominguez, Catherine; Keller, Eric N; Klein, Liore; Kim, Curi; Blood, Tim; Hyun, Judie; Williams, Thelonious W; Feldman, Katherine A; Mostafa, Heba H; et al.
Abstract: Among 9048 people infected with SARS-CoV-2 between January and May 2021 in Maryland, in regression-adjusted analysis, SARS-CoV-2 viruses carrying the spike protein mutation E484K were disproportionately prevalent among persons infected after full vaccination against COVID-19 compared with infected persons who were not fully vaccinated (aOR, 1.96; 95% CI: 1.36–2.83).